2021
DOI: 10.1111/jfpp.15985
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transglutaminase inhibits the deterioration of high‐temperature‐treated sea cucumber

Abstract: In this paper, the anti-deterioration effect of microbial transglutaminase (MTGase) on rehydrated sea cucumber was studied, and the effects of salt, sugar, and oil on the MTGase-treated sea cucumbers were also investigated. For all groups, the textural strength decreased with the storage time, but compared with the control group, the MTGase-treated group exhibited a significantly stronger texture profile (p < .05), higher thermal denaturation temperature of sea cucumber, lower protein degradation level (charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…With prolonged heat treatment, the porosity increased significantly ( P < 0.05) and reached a maximum of 63.37% ± 0.72% at 10 h heat treatment. Although the size of a single pore reached a maximum following 8 h of heat treatment, the number of pores was the largest and the porosity was highest when the heat‐treatment time was 10 h. The network structure was denser, and the porosity decreased when the heat‐treatment time was 12 h. The chemical bonds of the body wall were broken during heat treatment, and the collagen fibres and structure were destroyed (Liu et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…With prolonged heat treatment, the porosity increased significantly ( P < 0.05) and reached a maximum of 63.37% ± 0.72% at 10 h heat treatment. Although the size of a single pore reached a maximum following 8 h of heat treatment, the number of pores was the largest and the porosity was highest when the heat‐treatment time was 10 h. The network structure was denser, and the porosity decreased when the heat‐treatment time was 12 h. The chemical bonds of the body wall were broken during heat treatment, and the collagen fibres and structure were destroyed (Liu et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, deterioration of high‐pressure treated sea cucumbers was indicated more seriously because the drastic destruction of the body wall and collagen fibres was more severe than in traditional heating methods (Chen et al ., 2016). To address this issue, microbial transglutaminase (Liu et al ., 2021), celery and chlorogenic acid (Zhu et al ., 2022), lactic acid and tea polyphenols (Liu et al ., 2020a) have been used to delay softening and preserve the morphology of samples, thereby extending the quality retention period. In addition, the lipid oxidation characteristics of dried sea cucumbers during storage have been reported using an intelligent surgical knife coupled with a rapid evaporative ionisation mass spectrometry (iKnife‐REIMS) assessment method.…”
Section: Physical Changes Of Sea Cucumber During Thermal Treatmentmentioning
confidence: 99%
“…However, low‐temperature treatment can trigger endoenzyme activities, resulting in knotting of collagen fibres into spirals (Bi et al ., 2016). More severe collagen deterioration occurs during storage due to its degradation, oxidation and non‐enzymatic softening (Liu et al ., 2021, 2020a).…”
Section: Chemical Changes Of Sea Cucumber During Thermal Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Our early attempts using a Ca 2+ /phosphate 4 system and oxidized oligosaccharides 3 both (to some degree) suppressed non‐enzymatic deterioration, but were respectively limited by insufficient stabilization and a safety defect, which negates their potential as commercial food crosslinking agents. Recently, we reported that transglutaminase 5 could stabilize sea cucumbers, but later experiments found the stabilization was only effective for small sea cucumbers.…”
Section: Introductionmentioning
confidence: 99%